PERBEDAAN HASIL PEMERIKSAAN SDIDTK PADA BAYI YANG DIBERIKAN DAN TIDAK DIBERIKAN ASI EKSKLUSIF - Cahyaningrum, Etika Dewi; ., Ariyanti (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2016)
ABSTRACT: EXAMINATION RESULTS SDIDTK DIFFERENCES IN BABIES ARE GIVEN AND NOT GIVEN EXCLUSIVE BREAST. Stimulation Detection and Early Intervention Growth (SDIDTK) is an activity or investigation to find any irregularities early growth and development in toddlers and preschoolers. Toddlers aged 6-12 months at the health center II East Purwokerto totaled 154 toddlers. The purpose of this study is to describe the differences in the results of the examination SDIDTK in infants given and not given exclusive breastfeeding in Posyandu Mawar District of Mersi in 2015. The method in this research is a comparative descriptive with cross sectional approach. Data collection techniques using primary data obtained from respondents directly, secondary data in this study include the address of the respondent and the data number of mothers with babies ages 6-12 months. The sampling technique used purposive sampling, totaling 27 samples. SDIDTK examination results in infants breastfed exclusively based on measurements of weight/ height most of the normal total of 14 respondents (87.5%) and 2 babies were obese (12.5%). SDIDTK examination results in infants who are not breastfed exclusively based on the results of the weight/ height, head circumference examination, KPSP, and test the power to hear all that are in the normal category. Â Keywords: SDIDTK, Baby, exclusive breastfeeding, not exclusively breastfed